2018
DOI: 10.1159/000486826
|View full text |Cite
|
Sign up to set email alerts
|

Frontal White Matter Hyperintensity Is Associated with Verbal Aggressiveness in Elderly Women with Alzheimer Disease and Amnestic Mild Cognitive Impairment

Abstract: Background/Aims: Behavioral and psychological symptoms of dementia (BPSD) are exhibited in most patients with Alzheimer disease (AD). Although white matter hyperintensity (WMH) is often observed with AD, the precise role of WMH in BPSD remains unclear. The current study aimed to identify the impact of regional WMH on specific features of BPSD in persons with mild to moderate AD and amnestic mild cognitive impairment (aMCI). Methods: A sample of 256 female outpatients with AD (n = 217) and aMCI (n = 39) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
(94 reference statements)
2
9
0
Order By: Relevance
“…In the longitudinal mixed effect model, baseline WMH load was associated with significantly worse future NPI total scores (p=0.014), NPI irritability severity subscores (p=0.009), and there was a trend for worse future agitation (p=0.058). Our finding that the baseline whole brain WMH load was associated with increased future irritability severity scores supports previous findings (Boublay et al, 2016;Ogama et al, 2018;Misquitta et al, 2019 under review). One study found focal frontal WMH to be associated with verbal aggressiveness in amnestic MCI and AD (Ogama et al, 2018), which supports our current finding of the association between frontal lobe WMH load and worsening agitation and irritability.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the longitudinal mixed effect model, baseline WMH load was associated with significantly worse future NPI total scores (p=0.014), NPI irritability severity subscores (p=0.009), and there was a trend for worse future agitation (p=0.058). Our finding that the baseline whole brain WMH load was associated with increased future irritability severity scores supports previous findings (Boublay et al, 2016;Ogama et al, 2018;Misquitta et al, 2019 under review). One study found focal frontal WMH to be associated with verbal aggressiveness in amnestic MCI and AD (Ogama et al, 2018), which supports our current finding of the association between frontal lobe WMH load and worsening agitation and irritability.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that the baseline whole brain WMH load was associated with increased future irritability severity scores supports previous findings (Boublay et al, 2016;Ogama et al, 2018;Misquitta et al, 2019 under review). One study found focal frontal WMH to be associated with verbal aggressiveness in amnestic MCI and AD (Ogama et al, 2018), which supports our current finding of the association between frontal lobe WMH load and worsening agitation and irritability. Additionally, this finding echoes the results of Misquitta and colleagues (2019 manuscript under review), wherein they found WMH load to be a significant contributor to the NPI sub-syndrome of hyperactivity, which includes the following: agitation, euphoria, disinhibition, irritability, and aberrant motor behaviour.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Female aggression is considered to differ from male and findings from male samples can not apply to females [7]. Few studies mainly concerned manifestations of aggressiveness in women at various pathological conditions [8] or in women prisoners [7].…”
Section: Interrelationship Differences Between Personality Traits In mentioning
confidence: 99%
“…13 A close association has been identified between WMHs and dementia and neurodegenerative diseases, including Alzheimer disease and Parkinson disease. 46…”
Section: Introductionmentioning
confidence: 99%